LEARNER AUTONOMY USING 5E LEARNING CYCLE - Fauzi, Fatchul; Mustadi, Ali (Universitas Muhammadiyah Purwokerto, 2019)
This resarch aims to determine the effect of the 5E learning cycle on learner autonomy. Research with the type of quasi experiment using questionnaires as a measure of learner autonomy. The research subjects are 84 PGSD students. 5E Learning Cycle applicants with the syntax of Engagement, Exploration, Exploration, Elaboration, and Evaluation were carried out in advanced science courses in the second semester.. The results showed that the mean pre-test score of the control group and the experimental group had increased. The Mann-Whitney U test obtained a significance of 0.039 and the effect of the 5E learning cycle showed a high category with score of N gain is 0.98. So that it can be concluded that the 5E learning cycle affects student learner autonomy.